Atlas of anatomy : Latin Nomenclature (Thieme, 2022)
"An updated atlas that provides a clear, accurate, and fully illustrated guide to human anatomy, using Latin nomenclature"-- Quintessential Atlas of Anatomy expands on widely acclaimed prior editions! Atlas of Anatomy, Latin Nomenclature, Fourth Edition builds on its longstanding reputation of being the highest-quality anatomy atlas published to date using Latin nomenclature. With more than 2,000 exquisitely detailed illustrations, including over 120 new to this edition, the Atlas helps students and seasoned clinicians master the details of human anatomy. Key Features:NEW! Expanded Radiology sections include over 40 new radiographs, CTs, and MRIsNEW! A more dissectional approach to the head and neck region places neck anatomy before that of the head - the way most students dissectNEW! Additional images and tables detail the challenging anatomy of the peritoneal cavity, inguinal region, and infratemporal and pterygopalatine fossaeNEW! Almost 30 new clinical boxes focus on function, pathology, diagnostic techniques, anatomic variation, and moreNEW! More comprehensive coverage clarifies the complexities of the ANS, including revised wiring schematicsAlso included in this new edition:Muscle Fact spreads provide origin, insertion, innervation, and actionAn innovative, user-friendly format: every topic covered in two side-by-side pagesOnline images with "labels-on and labels-off" capability are ideal for review and self-testing What users say about the Atlas of Anatomy: "I can't say enough how much I like the organization of this text. I think Thieme has 'hit the nail on the head' with structuring everything by region (Lower Limb) and sub-region (Ankle & Foot). It's very easy to find what you're looking for." "The figures in the Atlas of Anatomy are exemplary and surpass other competing texts. The images are clear, precise, and aesthetically colored. The unique views presented in this work are also very helpful for studying a three-dimensional subject such as human anatomy." This book includes complimentary access to a digital copy on https://medone.thieme.com
Keywords: Anatomi.; Anatomy.; Atlases; Human anatomy; Human anatomy.